Anti-HMGCR Antibody-Positive Myopathy Shows Bcl-2-Positive Inflammation and Lymphocytic Accumulations. Issue 4 (25th February 2020) - Kurashige, Takashi; Murao, Tomomi; Mine, Naoko; Sugiura, Tomohito; Inazuka, Yukiko; Kuraoka, Kazuya; Takahashi, Tetsuya; Maruyama, Hirofumi; Torii, Tsuyoshi
Abstract: Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) and antisignal recognition particle (SRP) antibodies are frequently associated with immune-mediated necrotizing myopathy (IMNM). However, the difference in clinical manifestations between anti-HMGCR and anti-SRP antibodies is unclear. HMGCR is an essential enzyme for cholesterol biosynthesis and is inhibited by statins that regulate apoptosis of Bcl-2-positive and beta chemokine receptor 4 (CCR4)-positive lymphoma cells. In this study, we aimed to clarify Bcl-2 and CCR4 expressions of lymphocytes in anti-HMGCR antibody-positive IMNM and explore the difference between anti-HMGCR antibody-positive myopathy and other inflammatory myopathies. We retrospectively examined Bcl-2- and CCR4-positive lymphocyte infiltrations in muscle and skin biopsy specimens from 19 anti-HMGCR antibody-positive patients and 75 other idiopathic inflammatory myopathies (IIMs) patients. A higher incidence of Bcl-2- and CCR4-positive lymphocytes was detected in the muscle and skin of anti-HMGCR antibody-positive IMNM patients (p < 0.001). In 5 patients with anti-HMGCR antibodies, Bcl-2-positive lymphocytes formed lymphocytic accumulations, which were not observed in other IIMs. Low-density lipoprotein cholesterol levels were not increased except for patients with Bcl-2-positive lymphocytic accumulations (p = 0.010). Bcl-2 and CCR4 lymphocyte infiltrations could be a pathological characteristic of anti-HMGCR antibody-positive IMNM.